The Implementation of Authentic Assessment to Evaluate Students' Reading Comprehension at the Tenth Grade of SMAN 7 Padang - Mailisa Al Mirrah; M. Zaim (Universitas Negeri Padang, 2021)
An authentic assessment is a form of assessment to assess students' ability to use the language they learn in the actual context. An authentic assessment can be in the form of assessing the ability to understand what other people say both listening and reading. The implementation of authentic assessment is expected to improve the quality of assessment during the process of learning English. The researcher conducted the implementation of authentic assessment on reading comprehension in the tenth grade. This research used descriptive quantitative research. The population and sample of this study were tenth-grade students and English teachers at SMAN 7 Padang who taught in the tenth grade. The research instruments were a questionnaire, documentation, and interview. The result of the study found that (1)there were four forms of authentic assessment on reading comprehension used by the teacher at SMAN 7 Padang, (2)the level of difficulties in implementing the authentic assessment on reading comprehension is easy by the students, (3) the problem faced by the teacher in implementing the authentic assessment are students’ understanding about the authentic assessment and the differences between the curriculum in 2013.